MITIGATION OF FAULTY SPINAL POSTURES USING EXERCISES WITH HAND APPARATUS - Cristina Elena MORARU; Alice Viviana ŢOCU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Rhythmic gymnastics is among the sports causing faulty postures, characterized by exaggerated spinal curvatures or abnormal curvatures. The purpose of this paper is to ensure harmonious physical development, improved posture and maximum sports training efficiency. Through this paper, we propose to assess the hypothesis according to which the faulty spinal postures emerged in the female rhythmic gymnasts can be improved using exercises with portable apparatus, applied both prophylactically and correctively, to determine better posture. In this respect, we monitored a fourth-category gymnast aged 8, diagnosed with levoconvex dorsolumbar scoliotic posture and hyperlordotic posture. For measurements, the GPS 400 - Global Postural System stabilometric platform was used. Her therapeutic plan consisted of a three-month exercise program with portable apparatus, 3 time a week, 50 minutes each. After applying the program, we noted a frontal plane progress; at the initial test, the shoulder had a 3.5° depression, while 3° at the final one. Waist triangle - the right decreased to 1.8 cm at the final test, from 2 cm initially. The anterior superior iliac spine values improved from 2° to 2.5°, while subgluteal folds from 2° to 1.5°. In sagittal plane, we registered only lumbar improvement from 4.3 cm to 3.8 cm, while the cervical arrow had a constant 1.8 cm value in both tests. By using exercises with portable apparatus between the two tests, we note that the gymnast managed to improve her posture, confirmed by the values obtained in body alignment using the posturograph, which confirms the hypothesis of the paper.